Graphene nanoribbon ceramic composites. (August 2015) - Ramirez, C.; Osendi, M.I.; Miranzo, P.; Belmonte, M.; Figueiredo, F.; Castro-Beltrán, A.; Terrones, M.
Abstract: By unzipping multi-walled carbon nanotubes (MWCNTs) it is possible to obtain graphene nanoribbons (GNRs) that could then be used as fillers in ceramic composites. Here we report the fabrication of silicon nitride (Si3 N4 ) ceramics with different contents of GNRs by spark plasma sintering. The GNR fillers confer electrical conductivity to the Si3 N4 composites, following a semiconducting-like behavior at relatively low volume filler concentrations (0.04). In addition, a toughening effect, produced by GNRs bridging the cracks was observed. GNRs appear to be an efficient alternative to graphene-based composites, useful in the fabrication of novel multifunctional ceramic composites.